Answer:
measure of angle A is 80 degree.
Step-by-step explanation:
isosceles triangle will have same base angles
first base angle is 50, and the second will also be 50
3 angles of a triangle will add up to be 180 degree.
A is the vertex angle.
So 50 + 50 + A = 180
100 + A = 180
A = 80.
Answer: The graph in the bottom right-hand corner
(see figure 4 in the attached images below)
===========================================
Explanation:
Let's start off by graphing x+y < 1. The boundary equation is x+y = 1 since we simply change the inequality sign to an equal sign. Solve for y to get x+y = 1 turning into y = -x+1. This line goes through (0,1) and (1,0). The boundary line is a dashed line due to the fact that there is no "or equal to" in the original inequality sign. So x+y < 1 turns into y < -x+1 and we shade below the dashed line. The "less than" means "shade below" when y is fully isolated like this. See figure 1 in the attached images below.
Let's graph 2y >= x-4. Start off by dividing everything by 2 to get y >= (1/2)x-2. The boundary line is y = (1/2)x-2 which goes through the two points (0,-2) and (4,0). The boundary line is solid. We shade above the boundary line. Check out figure 2 in the attached images below.
After we graph each individual inequality, we then combine the two regions on one graph. See figure 3 below. The red and blue shaded areas in figure 3 overlap to get the purple shaded area you see in figure 4, which is the final answer. Any point in this purple region will satisfy both inequalities at the same time. The solution point cannot be on the dashed line but it can be on the solid line as long as the solid line is bordering the shaded purple region. Figure 4 matches up perfectly with the bottom right corner in your answer choices.
Answer:
The "check your answer" probably means check your answer by graphing.
Step-by-step explanation:
F(x) = x^2 + 3x + 2
if g(x) is the reflection of f(x) across the x - axis then
g(x) = -f(x)
g(x) = - (x^2 + 3x + 2)
g(x) = - x^2 - 3x - 2
Answer:
a₃₅ = 182
Step-by-step explanation:
There is a common difference d between consecutive terms, that is
d = 17 - 12 = 22 - 17 = 5
This indicates the sequence is arithmetic with n th term
= a₁ + (n - 1)d
where a₁ is the first term and d the common difference
Here a₁ = 12 and d = 5 , then
a₃₅ = 12 + (34 × 5) = 12 + 170 = 182